δ Subunit Inhibits Neurosteroid Modulation of GABA(A)Receptors - Zhu, Wei Jian (J Neurosci, 1996)
Neurosteroid modulation of GABA(A) receptors has been observed with all subunit combinations investigated; however, hetero-oligomeric GABA(A) receptors containing δ subunits were not studied previously. We describe the effect of δ subunit expression on 3α,21-dihydroxy-5α-pregnan-20-1 (THDOC)-induced potentiation of GABA-gated currents in transfected HEK 293 cells and in cerebellar granule cells in vitro. THDOC (100 nm) significantly potentiated GABA-gated currents in cells transfected with combinations of α1, α6, β3, and γ2 subunit cDNAs, whereas cotransfection of δ subunit cDNA inhibited this potentiation. In contrast, the direct Cl(−) channel activation by THDOC at higher concentrations (1–10 μm) was not significantly dependent on δ subunit cotransfection. These results suggest that the presence of the δ subunit inhibits GABA(A) receptor modulation but not the direct activation by neurosteroids. Cotransfection with δ subunit also affected the negative allosteric modulation by pregnenolone sulfate. THDOC potentiation of GABA-gated currents was greater in cerebellar granule cell cultures at 4 d in vitro(DIV) compared with those at 14 DIV. Single-cell reverse transcription-PCR analysis of the mRNAs expressed in cultured cerebellar granule cells shows that an increased number of granule cells at 14 DIV express δ subunit mRNAs as compared with 4 DIV granule cells. The presence of δ subunit mRNAs detected in individual cells correlated well with the lack of sensitivity to THDOC. These results suggest that developmental expression of GABA(A)receptor δ subunits may play an important role in determining the region-specific neurosteroid-induced modification of fast inhibitory synaptic function.